2021
DOI: 10.1111/fare.12573
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and Mental Health of Young Adult Children in China: Economic Impact, Family Dynamics, and Resilience

Abstract: Objective:The current study aimed to examine the economic impact of virus on family dynamics and college-age children's mental health in China and to identity personal and social or relational resilience factors that could buffer the negative consequences of COVID-19. Background: Since an outbreak of COVID-19 was first reported in China in December 2019, it has profoundly changed the lives of families and children of all ages. In particular, it has created challenges among families with college-age young adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The pandemic caused massive disruption to normal college life for students in China who may have experienced intense pressure arising from difficulties adapting to online modes of learning, leading to concerns and uncertainty about their academic performance ( Li et al., 2021 ; Son et al., 2020 ), their future and their educational prospects ( Cao et al., 2020 ), all of which increased the risk of suicide among college students. Moreover, a growing body of evidence supports the view that home quarantine might explain higher incidences of family conflict, as a result of more intense feelings of loneliness among college students who had a limited amount of personal space and were isolated from their peer groups during the COVID-19 lockdown ( Cui and Hong, 2021 ; Silk et al., 2021 ; Elbogen et al., 2021 ). Thus, there is an urgent need to develop psychological prevention measures that target students who have been particularly impacted during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic caused massive disruption to normal college life for students in China who may have experienced intense pressure arising from difficulties adapting to online modes of learning, leading to concerns and uncertainty about their academic performance ( Li et al., 2021 ; Son et al., 2020 ), their future and their educational prospects ( Cao et al., 2020 ), all of which increased the risk of suicide among college students. Moreover, a growing body of evidence supports the view that home quarantine might explain higher incidences of family conflict, as a result of more intense feelings of loneliness among college students who had a limited amount of personal space and were isolated from their peer groups during the COVID-19 lockdown ( Cui and Hong, 2021 ; Silk et al., 2021 ; Elbogen et al., 2021 ). Thus, there is an urgent need to develop psychological prevention measures that target students who have been particularly impacted during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Resilient communication was inversely related to relational uncertainty for married individuals during the first pandemic wave ( Lillie et al, 2021 ). Resilience was also associated with fewer negative parent-child interactions and less anxiety and depression in Chinese students who moved home due to COVID-19 ( Cui & Hong, 2021 ). Rivers and Sanford (2020) accordingly developed the Interpersonal Resilience Inventory and advocated for its use during the pandemic to capture the resiliency aspect, a unique component from other social support measures, that is central to navigating challenges of a long-term crisis such as the pandemic.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…In a study of 450 college students in the mid-Atlantic United States, an area hard-hit by the pandemic during 2020, results revealed that young adults reported increases in their inability to focus, increased anxiety and depression, and excess time spent searching for information about COVID-19 (Kecojevic et al 2020). A study with college students in China noted that family economic difficulties related to COVID-19 were related to parent-child relationship difficulties, which in turn were related to increases in self-reported anxiety and depression (Cui and Hong 2021).…”
Section: Covid-19 and Mental Healthmentioning
confidence: 99%